Markers of Oxidative Stress in the Exhaled Breath Condensate of Workers Handling Nanocomposites - Pelclova, Daniela; Zdimal, Vladimir; Schwarz, Jaroslav; Dvorackova, Stepanka; Komarc, Martin; Ondracek, Jakub; Kostejn, Martin; Kacer, Petr; Vlckova, Stepanka; Fenclova, Zdenka; Popov, Alexey; Lischkova, Lucie; et al. (Nanomaterials (Basel, Switzerland), 2018)
Researchers in nanocomposite processing may inhale a variety of chemical agents, including nanoparticles. This study investigated airway oxidative stress status in the exhaled breath condensate (EBC). Nineteen employees (42.4 ± 11.4 y/o), working in nanocomposites research for 18.0 ± 10.3 years were examined pre-shift and post-shift on a random workday, together with nineteen controls (45.5 ± 11.7 y/o). Panels of oxidative stress biomarkers derived from lipids, nucleic acids, and proteins were analyzed in the EBC. Aerosol exposures were monitored during three major nanoparticle generation operations: smelting and welding (workshop 1) and nanocomposite machining (workshop 2) using a suite of real-time and integrated instruments. Mass concentrations during these operations were 0.120, 1.840, and 0.804 mg/m³, respectively. Median particle number concentrations were 4.8 × 10⁴, 1.3 × 10⁵, and 5.4 × 10⁵ particles/cm³, respectively. Nanoparticles accounted for 95, 40, and 61%, respectively, with prevailing Fe and Mn. All markers of nucleic acid and protein oxidation, malondialdehyde, and aldehydes C₆⁻C13 were elevated, already in the pre-shift samples relative to controls in both workshops. Significant post-shift elevations were documented in lipid oxidation markers. Significant associations were found between working in nanocomposite synthesis and EBC biomarkers. More research is needed to understand the contribution of nanoparticles from nanocomposite processing in inducing oxidative stress, relative to other co-exposures generated during welding, smelting, and secondary oxidation processes, in these workshops.
Keywords: nanoparticles; inhalation; exhaled breath condensate; workers; nanocomposites; occupational exposure; oxidative stress